A model for Geant4-DNA to simulate ionization and excitation of liquid water by protons travelling above 100 MeV. (October 2022) - Domínguez-Muñoz, A.D.; Gallardo, M.I.; Bordage, M.C.; Francis, Z.; Incerti, S.; Cortés-Giraldo, M.A.
Abstract: Biological damage induced by ionizing radiation plays a major role in many application fields as radiotherapy and microdosimetry. Geant4-DNA Monte Carlo track-structure code has the capability to simulate the passage of radiation through liquid water, containing physical, physicochemical and chemical processes that lead the early DNA damage. For proton projectile, current models reach up to an incident energy of 100 MeV. In order to cover the entire energy regime involved in proton radiotherapy, this work presents a new model that extends proton ionization and excitation of liquid water up to 300 MeV. Calculation of cross section dataset is made for ionization of five ionization shells and five excitation levels of liquid water using the Relativistic Plane Wave Born Approximation (RPWBA). Implementation is validated through the spower and range examples of the official release, obtaining an agreement within 1% with respect to reference data published in ICRU90 report.